Pushing the Boundaries of Food Product Innovation Acceptance: A Case of Radical Ready-to-Eat Food Product Innovation in Malaysia - Wan Ismail, Wan Rusni; Che Ahmat, Nur Hidayah; Ramli, Rafidah Aida; Handajani, Sri; Ngelambong, Anderson (Information Management and Business Review, 2024)
This study examines the impact of food neophobia and food innovation on Malaysian consumer attitudes, subjective norms, perceived behaviour control, and consumer behaviour intention towards ready-to-eat (RTE) foods. Additionally, this study investigates the mediating effects of food innovation, attitude, subjective norms, and perceived behaviour control on the relationship between food neophobia and consumer behaviour intention. A quantitative cross-sectional study was used whereby an online survey was developed and disseminated via social media platforms to all Malaysian consumers aged 18 years and above from October 2023 to January 2024. A total of 321 valid responses were used for hypothesis testing using SPSS and MPlus software. This study found eleven out of nineteen proposed hypotheses were statistically significant. Food neophobia directly influences food innovation, attitude, subjective norms, and perceived behaviour control. More importantly, this study found the significant influence of attitude, subjective norms, and food innovation as mediators in influencing the association between food neophobia and consumer behaviour intention. Findings from this study contribute to the RTE food behavioural studies by incorporating the theory of planned behaviour and stimulus-organism-response models. This study also introduces attitude, subjective norms, and food innovation as mediators in influencing the association between food neophobia and consumer behaviour intention. Results from the integrated model provide a more comprehensive understanding of the impact of food neophobia and food innovation on consumer attitude, subjective norms, perceived behaviour control, and behaviour intention. Findings underline the importance of RTE food producers exploring young consumers as the new markets for their products.